2020
DOI: 10.1101/2020.06.15.152892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interfacial Water Molecules Make RBD of SPIKE Protein and Human ACE2 to Stick Together

Abstract: A novel coronavirus (SARS-CoV-2; COVID-19) that initially originates from Wuhan province in China has emerged as a global pandemic, an outbreak that started at the end of 2019 which claims 431,192 (Date: 15 th June 2020 (https://covid19.who.in) life till now. Since then scientists all over the world are engaged in developing new vaccines, antibodies, or drug molecules to combat this new threat. Here in this work, we performed an in-silico analysis on the protein-protein interactions between the receptor-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…Similar behavior has been seen in other simulations (Ghorbani et al, 2020; Spinello et al, 2020) with the difference likely explained by solution vs. crystallization conditions. Water molecules were observed at the interface in other simulations and are likely bridging the interactions (Malik et al, 2020), also underscoring the dynamic nature of the interactions (see below). To further indicate the overall stability of the interface in the simulations, we calculated the solvent accessible surface area, which is buried between the RBD and ACE2 proteins in the complex.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Similar behavior has been seen in other simulations (Ghorbani et al, 2020; Spinello et al, 2020) with the difference likely explained by solution vs. crystallization conditions. Water molecules were observed at the interface in other simulations and are likely bridging the interactions (Malik et al, 2020), also underscoring the dynamic nature of the interactions (see below). To further indicate the overall stability of the interface in the simulations, we calculated the solvent accessible surface area, which is buried between the RBD and ACE2 proteins in the complex.…”
Section: Resultsmentioning
confidence: 57%
“…Similarly, with the exception of the hBD-2 residue Arg23, which forms a hydrogen bond with the ACE2 residue Glu484 greater than 50% of the time, the occupancy of other hydrogen bonds is reduced compared to the reference complex. As before, the occupancy of these interactions is not 100%; i.e., more like 30%, suggesting that they are somewhat dynamic (see discussion below) and are accompanied by indirect H-bond interactions with water molecules near or at the interface bridging the interactions (Malik et al, 2020). Both of these features were also found in simulations of the RBD:ACE2 interaction, as already noted; however, the dynamics of these interactions appear to be more prevalent in the RBD:hBD-2 interaction.…”
Section: Resultsmentioning
confidence: 77%
“…The analysis revealed important electrostatic interaction around the 'Site 1' region. The majority of the interactions were formed by the residues Arg403, Ser494, Gly496, and Asn501 through direct and water-mediated hydrogen bond contacts (figure 7A, B) similar to the RBD-ACE2 contact (Malik et al 2020). The residues Tyr453, Gln494, Gly495, and Tyr505 contribute to the watermediated hydrogen bonding through most of the simulation.…”
Section: Cid9954003mentioning
confidence: 84%
“…This residue is V404 in SARS-COV which is not able to make any salt-bridge and does not make H-bond with ACE2. Gao et al 27 used a FEP approach and showed that mutation V404 to K417 lowers the binding energy of nCOV-2019 RBD to ACE2 by −2.2 ± 0.9 k cal/mol. A salt bridge between R426 on RBD and E329 on ACE2 stabilizes the complex in SARS-COV/ACE2.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the role of water-mediated interactions has been pointed out to be a driving force which is shown to be similar for both SARS-COV and nCOV-2019 RBD. 27 Spinello and co-workers 30 studied the binding of nCOV-2019 and SARS-COV RBD to ACE2 and found that the former binds its receptor with 30 k cal/mol higher affinity than SARS-COV RBD. Gao et al.…”
Section: Introductionmentioning
confidence: 99%